Acceptance of Christianity in Iceland in the year 1000 (999) - Gíslason, Jónas (Scripta Instituti Donneriani Aboensis, 1990)
No Christian mission was pursued among the Norse in Iceland before the latter part of the tenth century, and the ruling body of the Church took no part in this work. In the beginning, missionary activity was the private initiative of an Icelander, and the concluding chapter was supported by the Norwegian crown. Christian influence increased steadily then during this heathen period. The greatest hindrance to the propagation of Christianity among the Icelandic chieftains during the tenth century was undoubtedly the fact that Christians were denied seats in the legislative assembly; therefore it was not easy for the sons of the chieftains to be converted. Although pagans enjoyed a majority at the Althing in the year 1000, the Christians had increased their numbers. There was great danger of war in the land if agreement were not reached at the assembly. The choice consequently was either to reach an agreement or have a civil war, which would have led to the abrogation of the legal political and power structure. Older and peaceable chieftains wanted above all to protect the peace and they consequently accepted baptism and professed Christianity. This indicates that Christianity has had a great influence on Icelandic national life. The Christian conversion at the Althing in the year 1000 was, thus, both a religious and a political decision.